Analytical Solutions of the (2+1)-Dimensional Stochastic Chiral Nonlinear Schrödinger equation Using the Generalized (G’⁄G+A)-Expansion and Jacobi Elliptic Function Methods - Muna Ali Mansour; Fatma M. Ahmed; Mahmoud El-Horbaty (African Journal of Advanced Pure and Applied Sciences, 2026)
This study focuses on the (2+1)-dimensional stochastic Chiral Nonlinear Schrödinger equation, which incorporates a multiplicative Gaussian noise component. By applying the generalized (G’⁄G+A)-expansion method and the Jacobi elliptic function method, various accurate analytical solutions were derived, including bright solitons, Kink-type dark solitons, and periodic solitons. The research also evaluates the physical stability and structural integrity of these waves under the influence of random disturbances. Numerical simulations showed that the solutions obtained maintain their properties despite the presence of noise, which confirms the robustness of the analytical results. These results provide important insights into wave propagation in random nonlinear media, particularly in the fields of optical fibers and plasma physics.